Disparity of SED Recovery: Community Initiatives to Enhance a System of Care Mental Health Transformation. (March 2014) - Grape, Annette; Plum, Kathleen C.; Fielding, Stephen L.
How do youth from various community groups designated as having a serious emotional disturbance (SED) recover over time? We conducted an evaluation of a Substance Abuse and Mental Health Services Administration System of Care grant initiative for Monroe County, New York, to answer this and other questions. We looked at outcome differences over time using the Behavioral and Emotional Ratings Scale's (2nd ed.) overall strength scores among youth living in four geographical places at the start of services: high-income urban, low-income urban, suburban, and rural. Minorities (be they nonwhite or white) within each group, except suburban, had the higher probability of being designated as having SED. We found recovery disparities among white urban youth and their nonurban counterparts, and among nonwhite suburban and high-income urban youth and their low-income urban and rural counterparts. Applied implications include the following: (a) Continue the restructuring of mental health and juvenile justice agencies to become more culturally competent, (b) create a social marketing campaign to address the stigma surrounding mental illness, (c) build coalitions to publicize risk factors to mental health and their prevention, (d) restructure schools away from the prevailing eurocentric model of education, and (e) create a labor hour exchange for the repair and upgrade of housing and other infrastructure.